Effects of Inclusion of Processed Grapefruit Pulp on Wheat Flour Biscuit - Kayode, Roland Monday; Edem, Victor Ephraim; Ogundun, Niyi Julius; Ajibola, Rilwan Olaitan; Kayode, Bukola Idowu (Journal of Food Technology Research, 2020)
Biscuits were produced from the composite flour of grapefruit pulp and wheat flour. The Grapefruit pulp was boiled, fermented and some unfermented separately. Nine composite flours were made from the fermented, boiled and unfermented grapefruit pulp at different ratios of 10:90, 20:80 and 30:70 respectively while the control was 100% wheat flour. The proximate composition ranged from 6.50-8.25% (moisture), 5.46-11.36% (protein), 1.5-9.75% (crude fiber), 0.5-1.75% (ash), 2.93-4.35% (fat), and 62.77-80.04% (carbohydrate). The water absorption capacity and oil absorption capacity ranged from 1.01-1.42 g water/g flour and 0.94- 1.56 g oil/g flour respectively. The values obtained for fiber fraction analysis ranged from 24- 44% (neutral detergent soluble), 11-39.75% (acid detergent fiber), 6.50-34.50% (lignin), 2.75-6.63% (silica), 2.5-7.5% (cellulose) and 5.00-20.50% (hemicellulose). The sensory scores of the biscuits indicated that sample 10BGP had the best overall acceptability among the composite flour pointing out high acceptability at up to 10% inclusion of grapefruit pulp flour to wheat flour. This research recommended the inclusion of boiled grapefruit pulp flour up to 10% with wheat flour for the production of biscuit.